Pengembangan Modul Interaktif Mahasiswa PPG PAUD Terintegrasi Pembelajaran Berbasis Proyek sebagai Optimasi Pembelajaran Mahasiswa PPG di Sekolah Mitra - Ica Purnamasari; Umu Da'watul Choiro; Fikri Aulia; Eka Putri Surya; Alby Aruna; Adinda Marcelliantika (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This article discusses the development of an interactive module for early childhood education (PPG PAUD) students integrated with project-based learning as an effort to optimize learning in partner schools. The program aims to enhance the skills and understanding of PPG PAUD students through the use of interactive modules designed to support project-based learning. The methodology includes needs analysis, module design, implementation, and effectiveness evaluation. The results indicate that the interactive module significantly increases students' learning motivation, engagement, and material comprehension. Additionally, the integration of project-based learning allows students to develop practical skills relevant to the teaching context in partner schools. In conclusion, the development of interactive modules integrated with project-based learning provides a positive contribution to optimizing learning for PPG PAUD students.